2007
DOI: 10.1080/10550490701389658
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Olanzapine to Risperidone in Substance‐Abusing Individuals with Schizophrenia

Abstract: A 14-week double blind study compared the efficacy of olanzapine to risperidone in reducing marijuana/cocaine craving and use in individuals with schizophrenia. The study consisted of three phases: a two-week assessment phase, a two-week cross-taper phase onto olanzapine/risperidone, and a ten-week period of maintenance on olanzapine/risperidone. The proportion of cocaine-positive urines decreases over time for both groups with a trend for a greater reduction for the olanzapine group compared to risperidone gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 56 publications
0
48
0
1
Order By: Relevance
“…The atypical antipsychotics olanzapine and risperidone were compared for the management of psychosis in patients with a history of cannabis use (Akerele 2007; Robinson 2006; Van Nimwegen 2008). The two medications were found to have similar efficacy on psychotic symptoms with no evidence of a differential effect on cannabis craving or use.…”
Section: Discussionmentioning
confidence: 99%
“…The atypical antipsychotics olanzapine and risperidone were compared for the management of psychosis in patients with a history of cannabis use (Akerele 2007; Robinson 2006; Van Nimwegen 2008). The two medications were found to have similar efficacy on psychotic symptoms with no evidence of a differential effect on cannabis craving or use.…”
Section: Discussionmentioning
confidence: 99%
“…Another double-blind RCT in cocaine-dependent schizophrenia patients found significantly greater psychopathological improvement in the 'general psychopathology' subscale of the Positive and Negative Syndrome Scale (PANSS) and a significant reduction of craving, at least in one subscale (energy), with olanzapine than with haloperidol [41] . In a double-blind, randomized study comparing olanzapine with risperidone, the olanzapine group showed a trend towards a greater reduction of the proportion of cocaine-positive urines [42] .…”
Section: Second-generation Antipsychoticsmentioning
confidence: 98%
“…Four RCTs are available for olanzapine, three comparing olanzapine with haloperidol treatment [39][40][41] and one comparing olanzapine with risperidone [42] . In the first, randomized, double-blind study in patients with cannabisinduced psychosis, olanzapine was as effective as haloperidol but caused fewer EPS [39] .…”
Section: Second-generation Antipsychoticsmentioning
confidence: 99%
“…Unfortunately, available data are somewhat mixed and not overly promising (Green, Noordsy, Brunette, & O’Keefe, 2008) for risperidone (Green, Burgess, Dawson, Zimmet, & Strous, 2003; Smelson et al, 2002; Smelson et al, 2004), olanzapine (Akerele & Levin, 2007; M.F. Brunette et al, 2008; Noordsy et al, 2001; Petrakis, Leslie, Finney, & Rosenheck, 2006; Smelson et al, 2006), quetiapine (E.…”
mentioning
confidence: 99%